Computer networking : a top-down approach - Kurose, James F.; Ross, Keith W., 1956- (Boston : Addison-Wesley, 2010)
Building on the successful top-down approach of previous editions, the Fifth Edition of Computer Networking continues with an early emphasis on application-layer paradigms and application programming interfaces, encouraging a hands-on experience with protocols and networking concepts. With this edition, Kurose and Ross have revised and modernized treatment of some key chapters to integrate the most current and relevant networking technologies. Networking today involves much more than standards specifying message formats and protocol behaviors-and it is far more interesting. Professors Kurose and Ross focus on describing emerging principles in a lively and engaging manner and then illustrate these principles with examples drawn from Internet architecture.
Chapter 1 Computer Networks and the Internet -- Chapter 2 Application Layer -- Chapter 3 Transport Layer -- Chapter 4 The Network Layer -- Chapter 5 The Link Layer and Local Area Networks -- Chapter 6 Wireless and Mobile Networks -- Chapter 7 Multimedia Networking -- Chapter 8 Security in Computer Networks -- Chapter 9 Network Management -- Chapter 1 Computer Networks and the Internet -- Chapter 2 Application Layer -- Chapter 3 Transport Layer -- Chapter 4 The Network Layer -- Chapter 5 The Link Layer and Local Area Networks -- Chapter 6 Wireless and Mobile Networks -- Chapter 7 Multimedia Networking -- Chapter 8 Security in Computer Networks -- Chapter 9 Network Management
Includes bibliographical references and index.
1
Keywords: Internet; Computer networks